Tunable and precise two-bunch generation at FLASHForward. (July 2020) - Schröder, S; Ludwig, K; Aschikhin, A; D'Arcy, R; Dinter, M; Gonzalez, P; Karstensen, S; Knetsch, A; Libov, V; Lindstrøm, C A; Marutzky, F; Niknejadi, P; et al.
Abstract: Beam-driven plasma-wakefield acceleration based on external injection has the potential to significantly reduce the size of future accelerators. Stability and quality of the acceleration process substantially depends on the incoming bunch parameters. Precise control of the current profile is essential for optimising energy-transfer efficiency and preserving energy spread. At the FLASHForward facility, driver-witness bunch pairs of adjustable bunch length and separation are generated by a set of collimators in a dispersive section, which enables fs-level control of the longitudinal bunch profile. The design of the collimator apparatus and its commissioning is presented.